2010
DOI: 10.1111/j.1471-0528.2010.02660.x
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal complications increase the risk of postpartum depression. The Generation R Study

Abstract: Objective To examine whether specific pregnancy and delivery complications are risk factors for postpartum depression.Design A prospective longitudinal study.Setting Rotterdam, the Netherlands.Population A cohort of 4941 pregnant women who enrolled in the Generation R Study.Methods Information on perinatal complications was obtained from the midwife and hospital registries or by questionnaire. Logistic regression analyses were used to calculate the risk of postpartum depression for the separate perinatal compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
186
3
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(217 citation statements)
references
References 30 publications
12
186
3
16
Order By: Relevance
“…Women with a history of early onset PE report similar levels of psychosocial distress on average 14 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] years after pregnancy as measured by anxiety, (absence of) social support, and personality constructs optimism and Type D personality, when compared to a group without PE. A significantly higher level of depressive symptoms and fatigue was observed, albeit with a very small effect size.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Women with a history of early onset PE report similar levels of psychosocial distress on average 14 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] years after pregnancy as measured by anxiety, (absence of) social support, and personality constructs optimism and Type D personality, when compared to a group without PE. A significantly higher level of depressive symptoms and fatigue was observed, albeit with a very small effect size.…”
Section: Discussionmentioning
confidence: 97%
“…In a systematic review on this topic, Delahaije and colleagues described six studies on anxiety, depression, and PTSD in women following PE. Two studies were prospective [13,16], and four utilized a historic cohort [15,[17][18][19]. Depressive symptoms, PTSD, or anxiety were assessed a few months up to on average seven years after pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…In births that produce neonatal complications (foetal suffering or hospitalization of the new-born) there is an increase of depressive symptoms (Blom et al, 2010). Other variables, such as multiple births don't seem to have such a clear influence, as some researchers have found that there is an increase in the risk of depression (Mayberry et al, 2007) whilst others have found the contrary (Barbadoro et al, 2012).…”
Section: Socio-demographic and Clinical Variables And Postnatal Deprementioning
confidence: 91%
“…Laiku nepastebėta ir negydyta depresija kenkia motinos ir kūdikio gerovei. Tai gali užkirsti kelią moteriai atliekant kasdieninę veiklą, palaikant ryšį su savo vaiku ar artimais šeimos nariais (5). Deja, didelei daliai moterų depresija nėra teisingai diagnozuojama.…”
Section: įVadasunclassified
“…vidutinis), tuo tarpu tarp moterų, nepatyrusių komplikacijų, depresijos simptomų išreikštumas nustatytas 38,9 proc. moterų (5,6 proc. ryškus ir 33,3 proc.…”
Section: Rezultatai Ir Jų Aptarimasunclassified